The Language of Ecopoetry and the Transfer of Meaning - O'Loughlin, Cassandra J. (The Trumpeter, 2022)
This article explores the properties of ecopoetry that have to do with the realisation that we are not merely external observers but active and intrinsic participants within the biosphere. The type of ecopoetics I am advocating takes a subjective stance to experience: it begins from within individual consciousness and is rooted in sensory perception. Reference to the world through this type of ecopoetry evokes a tone or mood, or “atmosphere” between environmental attributes and human experience that can solicit an emotional response. Ecopoetry can deliver meaning on a level beyond the direct connotations of the signs and symbols on the page. This has to do with “presence” as a phenomenological approach to the aesthetics of nature. Employing these concepts has the potential to bridge the gap between nature and politics, and influence attitudes towards living sustainably with the earth.